Opinion 2482: Orchestes Illiger, 1798 (Insecta, Coleoptera, Curculionoidea, Curculionidae): name conserved by conditional reversal of precedence with respect to Salius Schrank, 1798 - ICZN (Bulletin of Zoological Nomenclature, 2021)
The International Commission on Zoological Nomenclature has conserved current usage of the generic name Orchestes Illiger, 1798 (Curculionoidea, Curculionidae), by giving it precedence over the little-used older name Salius Schrank, 1798 whenever these names are considered to be synonyms.
Keywords: Nomenclature; taxonomy; Coleoptera; CURCULIONOIDEA; CURCULIONIDAE; Orchestes; Salius; weevil